Analysis of electrical resistivity data in resolving the saline and freshwater aquifers in west coast Maharashtra - Gupta, Gautam; Maiti, Saumen; Erram, Vinit C. (My University, 2014)
Electrical resistivity methods are widely used for identification of groundwater potential zones and in delineating the lateral and vertical distribution of sub-surface. This method can also characterize the ingress of sea water into inlands thereby getting mixed up with fresh water bodies. The present studies are an attempt to delineate the saline water and fresh water intrusion in parts of Kudal-Vengurla and surrounding coastal region of western Maharashtra. A total of 30 vertical electrical soundings were carried out in a near grid pattern using the Schlumberger configuration. The contour maps for Dar-Zarrouk parameters viz. the transverse resistance (T), longitudinal conductance (S), transverse resistivity (ρt) and longitudinal resistivity (ρl) were computed to generate the resistivity regime of saline and fresh water bearing formations. The results illustrate that the Dar-Zarrouk parameters provide a constructive solution in delineating the saline and fresh water aquifers, particularly when the resistivity data interpretation encounters constraints due to intermixing of saline water aquifers, fresh water aquifers etc. The pseudo cross-sections of resistivity data over five profiles in the study region show the flow of saline water from the coastal side, partly controlled by the lineaments.
Keywords: Resistivity; Dar-Zarrouk parameters; Aquifer; Konkan; Maharashtra